Celebrity Ad Campaigns: How Celebrities are leveraged by Indian Corporates - Wij, Shaina (British Journal of Marketing Studies, 2023)
This research paper delves into the role of Indian celebrities in brand endorsements and their ROI to brands. As celebrity endorsements are one of the most preferred marketing tactics of brand managers, it is important to evaluate their effect on the target consumer. Some questions like, does a celebrity face help to drive sales? Or is the brand value of a company directly proportionate to the stature of the celebrity associated with it? Or Does a popular face bring instant publicity for the brand? This research paper gathers insight from young Indians, middle-aged adults and Indian marketing experts to find out brand recognition and popularity basis its celebrity association. The paper also deep dives into the perception of the brand when the associated celebrity is surrounded by scandals and bad press. Citation: Wij S. (2022) Celebrity Ad Campaigns: How Celebrities are leveraged by Indian Corporates, British Journal of Marketing Studies, Vol. 11, Issue 1, pp.,1-11